Makna Pertemanan Bagi Generasi Z: Studi Kualitatif Tentang Relasi Sosial Di Era Digital - Annisa, Nurin; Kurniadi, Ryan (CV RIFAINSTITUT, 2025)
Generation Z experiences friendship in a hybrid space that combines online and face-to-face interactions. Digital platform culture with various social metrics creates new dynamics in friendship relations, generating tensions between authenticity and performativity, closeness and privacy, as well as support and social fatigue. This study aims to provide a comprehensive understanding of the phenomenon of friendship among Generation Z which cannot be separated from the digital context, as well as provide insight into the complexities and challenges they face in building social relationships in the social media era. The research employs a qualitative approach with a multi-case design. Informants aged 18 to 26 years were selected purposively to represent variations in gender, social background, and platform usage patterns. Data were collected through semi-structured in-depth interviews, light digital ethnography, and daily journals of friendship interactions over one week. Data analysis was conducted using thematic analysis through open coding, category grouping, and cross-case theme extraction. Research findings indicate that friendship is defined as a safe space for self-expression, exchanging emotional support, learning, and collaborating. Relations move bidirectionally between digital platforms and physical meetings that mutually reinforce each other. Generation Z manages authenticity through audience settings, alternative accounts, and privacy boundary negotiations. Social metrics function as signals of care but also trigger comparison anxiety. Algorithms and platform culture influence the intensity and depth of interactions. This study concludes that Generation Z friendship constitutes a support network and identity formation arena that is consciously managed, requiring digital literacy and balance between online and offline interactions to prevent performative burden.